The magic kingdom [large type] - Banks, Russell, 1940-2023 (Thorndike Press, a part of Gale, a Cengage Company, 2023)
"In 1971, a property speculator named Harley Mann begins recording his life story onto a reel-to-reel machine. Reflecting on his childhood in the early twentieth century, Harley recounts that after his father's sudden death, his family migrated down to Florida's swamplands--mere miles away from what would become Disney World--to join a community of Shakers. Led by Elder John, a generous man with a mysterious past, the colony devoted itself to labor, faith, and charity, rejecting all temptations that lay beyond the property. Though this way of life initially saved Harley and his family from complete ruin, when Harley began falling in love with Sadie Pratt, a consumptive patient living on the grounds, his loyalty to the Shakers and their conservative worldview grew strained and, ultimately, broke. As Harley dictates his story across more than half a century--meditating on youth, Florida's everchanging landscape, and the search for an American utopia--the truth about Sadie, Elder John, and the Shakers comes to light, clarifying the past and present alike. A dazzling tapestry of love and faith, memory and imagination, The Magic Kingdom questions what it means to look back and accept one's place in history. With an expert eye and stunning vision, Russell Banks delivers a wholly captivating portrait of a man navigating Americana and the passage of time" --